Estimation of CO2 Emission Factors For Motorcycle and Passenger Car Use The International Vehicle Emissions Model in Banda Aceh - Hafsha, Hafsha Yanti Siregar; Sugiarto; Sofyan M. Saleh (Jurnal Serambi Engineering, 2025)
Private transportation is one of the main sources of emissions in Indonesia, which contributes to an increase in greenhouse gases due to excessive CO₂ emissions. This research aims to create a database of motorbike and passenger car activity, determine the CO₂ emission factor from various types of vehicles, and analyze the total CO₂ emissions from motorbikes and passenger cars in Banda Aceh. Data was collected through three survey methods: questionnaire, video, and GPS Logger. Questionnaires were distributed via Google Form to 400 respondents to determine patterns of use of motorbikes and passenger cars. Video surveys analyze traffic composition, while GPS Loggers are used to map driving conditions on Banda Aceh's arterial roads. The data obtained was then analyzed using descriptive statistics and the International Vehicle Emissions (IVE) model to calculate the emission factors for motorbikes and passenger cars in Banda Aceh City. The average Vehicle Specific Power (VSP) value for motorbikes was recorded at 1,449 kW/ton, while for passenger cars it was 1,456 kW/ton. The average CO₂ emission factor for motorbikes is 6.26 gr/km/hour per vehicle, and for passenger cars it reaches 51.54 gr/km/hour per vehicle. This CO₂ emission factor is relatively low in Banda Aceh. CO₂ emission predictions based on traffic volume show average motorbike emissions of 12.81 kg/km/hour, while passenger cars reach 72.83 kg/km/hour.